Bilateral ectropion in a 3 months old baby with lamellar ichthyosis: a rare case report - Kumar, Sweta S.; Raj, Shailly; Sami, Ifsa; Singh, Sonali (International Journal of Research in Medical Sciences, 2017)
Ichthyosiform dermatoses are a group of hereditary disorders characterized by dryness and roughness of the skin with excessive accumulation of epidermal scales. Four main types of Ichthyosis are Ichthyosis vulgaris, x-linked recessive, lamellar ichthyosis and epidermolytic hyperkeratosis. Lamellar ichthyosis is the rarest form with an incidence of 1 in 3, 00,000. It has autosomal recessive inheritance. Ocular manifestations include exposure keratitis secondary to ectropion, unilateral megalocornea, and enlarged corneal nerve, and blepharitis, absence of the meibomian gland, trichiasis, madarosis and absence of lacrimal puncta. Ectropion of both upper and lower lids have been documented. We are reporting a rare case of lamellar ichthyosis with bilateral upper eyelid ectropion in a child.